Analisis Likuiditas, Pertumbuhan, dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening di Sektor Konsumsi Tahun 2020-2024 - Anasya Risquita; Desi Ika (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the influence of liquidity, firm growth, and firm size on firm value with profitability as a mediating variable. The research applies a quantitative approach with a population of 129 consumer goods sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Samples were selected using purposive sampling, resulting in 50 companies that met specific criteria. Data were analyzed using SPSS version 26 through multiple linear regression, path analysis, and the Sobel test. The findings reveal that liquidity significantly affects profitability, while firm growth and firm size show no significant effect. Furthermore, liquidity, firm growth, and firm size do not have a direct impact on firm value, whereas profitability demonstrates a positive and significant influence. Mediation analysis further indicates that profitability mediates the relationship between liquidity and firm value but does not mediate the effect of firm growth or firm size on firm value. These results highlight the critical role of profitability in strengthening the link between liquidity and firm value, suggesting that improving profitability can serve as an effective strategy to enhance firm value, particularly in the consumer goods sector.